Pemahaman Penelitian Mahasiswa Pada Mata Kuliah Metode Penelitian Kualitatif - Manja (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to understand students’ mastery of research in the Qualitative Research Methods course. The method used is field research. The study adopts a descriptive approach with a qualitative research design. Data were obtained from sixth-semester students of the Islamic Guidance and Counseling Study Program at the Faculty of Islamic Studies, Sultan Muhammad Syafiuddin Sambas University. In collecting the data, the researcher employed observation, interviews, and documentation techniques. The data analysis techniques used in this study include data reduction, data presentation, verification, and drawing conclusions. To ensure data validity, triangulation techniques and member checks were applied. The findings indicate that students have understood the Qualitative Research Methods course, although their understanding is not yet highly comprehensive. Students must be able to grasp research methods because, at the end of their studies and after graduation, they are expected to become researchers in accordance with their respective fields of expertise